Abiotrophy in domestic animals: a review. - de Lahunta, A (1990)
This review of abiotrophies in domestic animals has been organized by the predominate anatomical location of the lesion. Secondary considerations include the major signs of the clinical disorder and special neuropathological features. Those abiotrophies that have an established genetic basis are identified but the review includes degenerative disorders in which the etiology is not yet established.